Physical exercise associated with NO production: signaling pathways and significance in health and disease - Dyakova, Elena Y.; Kapilevich, Leonid V.; Shylko, Victor G.; Popov, Sergey V.; Anfinogenova, Yana (Frontiers in Cell and Developmental Biology, 2015)
Here we review available data on nitric oxide (NO)-mediated signaling in skeletal muscle during physical exercise. Nitric oxide modulates skeletal myocyte function, hormone regulation, and local microcirculation. Nitric oxide underlies the therapeutic effects of physical activity whereas the pharmacological modulators of NO-mediated signaling are the promising therapeutic agents in different diseases. Nitric oxide production increases in skeletal muscle in response to physical activity. This molecule can alter energy supply in skeletal muscle through hormonal modulation. Mitochondria in skeletal muscle tissue are highly abundant and play a pivotal role in metabolism. Considering NO a plausible regulator of mitochondrial biogenesis that directly affects cellular respiration, we discuss the mechanisms of NO-induced mitochondrial biogenesis in the skeletal muscle cells. We also review available data on myokines, the molecules that are expressed and released by the muscle fibers and exert autocrine, paracrine and/or endocrine effects. The article suggests the presence of putative interplay between NO-mediated signaling and myokines in skeletal muscle. Data demonstrate an important role of NO in various diseases and suggest that physical training may improve health of patients with diabetes, chronic heart failure, and even degenerative muscle diseases. We conclude that NO-associated signaling represents a promising target for the treatment of various diseases and for the achievement of better athletic performance.